Hubungan Dukungan Keluarga Dengan Kesehatan Mental Pada Remaja Di SMPN 39 Kota Padang - Maharani, Saskia; Arianti, Diana; Gusdiansyah, Edo (Jurnal Sains Farmasi Dan Kesehatan, 2026)
Adolescence is a vulnerable period for mental health issues. Adolescent mental health is greatly influenced by the support provided by the family. Lack of family support can increase the risk of mental disorders such as depression and anxiety. In Indonesia, one in three adolescents has mental health issues. In West Sumatra, approximately 12% of adolescents exhibit symptoms of anxiety or depression. This study aims to investigate the relationship between family support and mental health among adolescents at SMPN 39 Kota Padang. The research method is descriptive analytical with a cross-sectional approach. The study population consisted of 125 eighth-grade students at SMPN 39 Kota Padang. The sampling technique used proportional random sampling, resulting in 56 participants, calculated using the Slovin formula. Data were collected over two days on April 24–25, 2025. Data analysis was conducted using univariate and bivariate methods. Based on the results of the study, it was found that 37.5% of respondents fell into the category of low mental well-being, and 35.7% of respondents fell into the category of insufficient family support. The chi-square test results showed a significant relationship between family support and adolescent mental health with a p-value of 0.023 (p < 0.05). Based on the research results, it can be concluded that there is a relationship between family support and mental health among adolescents at SMPN 39 Padang City. Improving students' mental health can be achieved through guidance and counseling services involving parents, educational activities and mental health counseling, as well as the development of extracurricular activities in sports and the arts.